2022
DOI: 10.3390/jcm11051236
|View full text |Cite
|
Sign up to set email alerts
|

A Tailored Lipid Supplement Restored Membrane Fatty Acid Composition and Ameliorates In Vitro Biological Features of Human Amniotic Epithelial Cells

Abstract: Cell culture conditions influence several biological and biochemical features of stem cells (SCs), including the membrane lipid profile, thus limiting the use of SCs for cell therapy approaches. The present study aims to investigate whether the in vitro culture may alter the membrane fatty acid signature of human Amniotic Epithelial Cells (hAECs). The analysis of the membrane fatty acid composition of hAECs cultured in basal medium showed a loss in polyunsaturated fatty acids (PUFA), in particular in omega-6 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…For an example, excessive ROS accumulated in trappc9-deficient ASCs might constantly damage DNA molecules and subsequently initiate cellular senescence [51]. A study reported that lipid balance was important to delaying the cellular senescence of human amniotic epithelial cells [52]. Hence, lipid metabolism disturbance seen in trappc9null ASCs may contribute significantly to the premature cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…For an example, excessive ROS accumulated in trappc9-deficient ASCs might constantly damage DNA molecules and subsequently initiate cellular senescence [51]. A study reported that lipid balance was important to delaying the cellular senescence of human amniotic epithelial cells [52]. Hence, lipid metabolism disturbance seen in trappc9null ASCs may contribute significantly to the premature cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…However, they need to be expanded in vitro to obtain a sufficient number of cells for transplantation. During the in vitro culturing, stem cells undergo replicative senescence [ 87 , 88 ], a process that can be triggered by elevated ROS levels [ 89 , 90 ]. In 2013, a protective role of PB against senescence in human amniotic stem cells was proposed [ 89 ].…”
Section: The Role Of Pb In Stem Cells and In Cell Senescencementioning
confidence: 99%
“…Regarding the relevance of the culture medium, we also reported that during in vitro culture in traditional medium, AECs lose their native membrane lipid profile, with a decrease in polyunsaturated fatty acid (PUFA) content and particularly in omega 6. The changes in the AEC fatty acid profile caused the onset of senescent features, including an increase in cell dimension and the expression of senescence-associated genes such as p16 [ 35 ].…”
Section: Oxidative Stress and Perinatal Cellsmentioning
confidence: 99%
“…The addition of a lipid supplement restored the AEC membrane fatty acid content, increasing the omega-6 percentage to physiological values. The recovery of an in vivo-like membrane fatty acid profile delayed the onset of senescence features and enhanced the immunomodulatory ability of AECs compared with standard culture conditions [ 35 ].…”
Section: Antioxidants For Perinatal Cellsmentioning
confidence: 99%